Chemical structure and biological properties of a polysaccharide isolated from Pleurotus sajor-caju. Issue 35 (2nd July 2019) - Seedevi, Palaniappan; Ramu Ganesan, Abirami; Mohan, Kannan; Raguraman, Vasantharaja; Sivakumar, Murugesan; Sivasankar, Palaniappan; Loganathan, Sivakumar; Rajamalar, Palasundaram; Vairamani, Shanmugam; Shanmugam, Annaian
Abstract : Herein, a polysaccharide obtained from Pleurotus sajor-caju was fractionated via anion-exchange column chromatography and purified using gel permeation column chromatography. Abstract : Herein, a polysaccharide obtained from Pleurotus sajor-caju was fractionated via anion-exchange column chromatography and purified using gel permeation column chromatography. The chemical characterization of the polysaccharide indicated that it contained 90.16% total carbohydrate, 0% protein, 12.7% ash and 5.2% moisture; on the other hand, the carbon, hydrogen and nitrogen contents were found to be 31.53, 4.28 and 3.01%, respectively. The polysaccharide has the molecular weight of 79 kDa; the chemical structure of the polysaccharide is →6)α-d -Glc iv (1→6)α-d -Glc iii (1→6)β-d -Glc ii (1→6)α-d -Glc i (1→units. The polysaccharide exhibited the DPPH radical scavenging activity of 21.67–68.35% at 10–160 μg ml −1, ABTS radical scavenging activity of 16.01–70.09% at 25–125 μg ml −1, superoxide radical scavenging activity of 24.31–73.64% at 50–250 μg ml −1, hydroxyl radical scavenging activity of 16.64–63.51% at 25–125 μg ml −1 and reducing power of 0.366–1.678% at 10–120 μg ml; further evaluation of the polysaccharide revealed its anticancer activity of 18.61–63.21% at 100–500 μg ml −1 concentration against the AGS human gastric carcinoma cell line. The active principle of the polysaccharide may be used in the food and pharmacological industry in the future.